SOCIAL, ECONOMIC AND POLITICAL SITUATION IN THE COUNTRIES OF THE MIDDLE EAST AND NORTH AFRICA AFTER THE «ARAB SPRING» (Journal of Oriental Studies, 2019)
«Arab spring» which led to significant social and political changes in a number of Arab countries  and largely influenced the global situation in the world, continues to be the most urgent topic for re- searchers - orientalists. Along with the term «Arab Spring», another researchers use «Arab awakening», «Arab’s develop», spring of An attempt is made to make a comprehensive analysis of the root causes and the double forces of the Arab Spring in this article. An analysis of the socio-economic, political and religious situation in every country, the influence of internal and external factors, is provided to provide an objective picture of the events, based on scientific methodology, documentary sources and scientific literature. The article selected countries, which the most vividly manifested different variants of the «Arab spring».Key words: countries of the Middle East and North Africa, «Arab Spring», armed conflicts, political life, social situation.